A Study on Consumer Switching Behavior Among Online Retailers in India - Chand, Nishant (2015)
66% of consumers switched companies in at least one of ten industries due to poor service in the past year. 82% of consumers felt their service provider could have done something to prevent switching. 55% say they’d have stayed if the company had proactively contacted them, and 51% would have stayed had the company simply recognized them and rewarded them for their business (Accenture Global Consumer Pulse Research, 2013). In the booming of age of organizations expanding their operations globally and companies diversifying their services and products, the only constant and critical aspect is - customer. One such booming nation is India where with improvement and penetration of internet, E-commerce is emerging as one of the biggest industry. However as it is still a new player, there is doubt of what Indian consumers seek in these online retailers to be loyal. The objective of this research is to study the consumer switching behavior among Indian online retailers. It not only focuses on the various factors which influence customers to skip from one e-retailer to another, but also why they choose to remain loyal. It also gives a perception of Indian online consumers on how they see customer value and E-service quality. Data for this research was collected via online survey questionnaire from 163 consumers in India. The results show that Indian consumers perceive high standards towards E-service quality and privacy is incredibly important to them. Most of the respondents were happy with their current “favorite” online retail but emphasized that they would make a switch on few reasons. The one reason which is most crucial is ethical issues. The findings of the research also show that price and promotion is least influential in order to choose another retailer.